Phylogenetic characterization of Cochroaches (Insecta: Blattaria) in Türkiye and determination of their vector potential for medically important parasites - Cevahir, Fatma; Düzlü, Önder; Atelge, Mübeccel; Yıldırım, Alparslan (Veterinary Journal of Ankara University, 2024)
This study was performed to investigate the phylogenetic characters of the cockroaches in the Kayseri region for mitochondrial cytochrome c oxidase subunit I (mt-COI), mt-COII, and internal transcribed spacer-2 (ITS-2) gene regions. It was also aimed to determine their mechanical transmission of medically important parasites. PCR-restriction fragment length polymorphism (RFLP) was performed by using mt-COI, mt-COII, and ITS-2 DNA gene regions to identify cockroach species (n=220) collected from different regions. Differentiation of cockroach species was based on RFLP models using two restriction enzymes: AvaI and EciI. For phylogenetic analysis, mt-COI, mt-COII, and ITS-2 DNA barcode regions were amplified with standard primers. The obtained amplicons were purified and sequenced using the PCR primers. According to PCR-RFLP, the cockroach species were identified as Blattella germanica (n=105), Blatta orientalis (n=86), and Periplaneta americana (n=29). A total of 13 haplotypes were detected and maximum likelihood (ML) analyses revealed that the sequences of all three species showed a monophyletic structure for the three gene regions. The cockroaches were examined for the presence of parasites. It was found that of the 58 parasitic forms identified, 46 (79.3%) belonged to helminth species and 12 (20.7%) to protozoan species. The results showed that B. germanica (58.6%) had the highest prevalence, followed by Bl. orientalis (32.8%) and P. americana (8.6%). The results of the study not only contribute to the molecular epidemiology of cockroaches but also confirm their important role as mechanical vectors of protozoan and helminth parasites.
Keywords: Cockroach; mt-COI and mt-COII; DNA barcoding; Veteriner Parazitoloji; Vector; Veterinary Parasitology; Cockroach; DNA barcoding; ITS-2; mt‐COI and mt‐COII; Vector; ITS-2